Artificial Intelligence: Studi Sensus Communis Nicolaus dari Cusa bagi Formasi Kaum Religius - Oktavianus Reinaldo Kalas; Markus Dolu Namang; Petrus Selestiano Lagut (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This article examines the relationship between Artificial Intelligence (AI), the concept of sensus communis proposed by Nicholas of Cusa (1401–1464), and the formation of religious communities. Through a theoretical-philosophical analysis, the author argues that sensus communis as the integrative capacity of the human intellect that unifies sensory, rational, and intuitive dimensions offers a normative epistemological framework for critically addressing the reductionism inherent in algorithmic AI. The main finding indicates that AI constitutes only a partial simulacrum of the integrative capacity of human reason and, therefore, cannot replace the ontological-transcendental dimension of authentic formation. Accordingly, this article proposes a model of critical-integrative formation grounded in three pillars: the selective use of AI, the preservation of AI-free spaces, and hermeneutical integration. The relevance of Cusa’s thought for contemporary religious formation is articulated in three contributions: docta ignorantia as a formative habitus, coincidentia oppositorum as a paradigm of dialogue, and ontological participation as the foundation of knowledge.